Historical imagination - Staley, David J., 1963- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines the threshold between what historians consider to be proper, imagination-free history and the malpractice of excessive imagination, asking where the boundary between the two sits and the limits of permitted imagination for the historian. Supporting theory with relatable examples, it shows how historical works are a complex combination of mimetic and creative imagination and offers a heuristic for assessing this ratio. Setting out complex theoretical concepts in an accessible and understandable manner and encouraging the reader to consider both the nature and limits of historical imagination, it is ideal for students and scholars of the philosophy of history"--
Introduction: Imagination in history -- Imagination in the archives -- Insertions -- The modal mood in historical writing -- The historian's fancy -- What if?
OCLC-licensed vendor bibliographic record.
Keywords: Historiography; Imagination; HISTORY / Historiography; HISTORY / Study & Teaching; HISTORY / General